Highly Anisotropic Conductors. Issue 41 (18th September 2017) - Wan, Jiayu; Song, Jianwei; Yang, Zhi; Kirsch, Dylan; Jia, Chao; Xu, Rui; Dai, Jiaqi; Zhu, Mingwei; Xu, Lisha; Chen, Chaoji; Wang, Yanbin; Wang, Yilin; et al.
Abstract: Composite materials with ordered microstructures often lead to enhanced functionalities that a single material can hardly achieve. Many biomaterials with unusual microstructures can be found in nature; among them, many possess anisotropic and even directional physical and chemical properties. With inspiration from nature, artificial composite materials can be rationally designed to achieve this anisotropic behavior with desired properties. Here, a metallic wood with metal continuously filling the wood vessels is developed, which demonstrates excellent anisotropic electrical, thermal, and mechanical properties. The well‐aligned metal rods are confined and separated by the wood vessels, which deliver directional electron transport parallel to the alignment direction. Thus, the novel metallic wood composite boasts an extraordinary anisotropic electrical conductivity (σ|| /σ⊥ ) in the order of 10 11, and anisotropic thermal conductivity (κ|| /κ⊥ ) of 18. These values exceed the highest reported values in existing anisotropic composite materials. The anisotropic functionality of the metallic wood enables it to be used for thermal management applications, such as thermal insulation and thermal dissipation. The highly anisotropic metallic wood serves as an example for further anisotropic materials design; other composite materials with different biotemplates/hosts and fillers can achieve even higher anisotropic ratios, allowing them to be implemented in a variety of applications. Abstract : Highly anisotropic metallic wood is fabricated by taking advantage of wood's naturally aligned and hierarchically structured channels. This novel metallic wood composite displays anisotropic electrical and thermal conductivity ratios as high as 10 11 and 18, respectively. The aeolotropic properties exhibited by metallic wood open opportunities in applications such as thermal management and electronic plants.